Szenario-Technik - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (Integrated Design Engineering. Ein interdisziplinäres Modell für die ganzheitliche Produktentwicklung, Kapitel: 20)

Responsibility Assignment in Systems Engineering - Gräßler, Iris; Thiele, Henrik; Grewe, Benedikt; Hieb, Michael (Proceedings of the Design Society)
Abstract Increasing system complexity can be controlled by using systems engineering processes. INCOSE defines processes with inputs and outputs (artifacts) for this purpose. Specific SE roles are used to organize the tasks of the processes within the company. In this work, the responsibilities for artifacts are evaluated by means of the RACI scheme and examined by a cluster analysis and discussed for a SE transformation project with a German automotive OEM. As a result of the study, the optimal composition for systems engineering teams is identified and the systems engineering roles are prioritized.
Keywords: systems engineering (SE); project management; model-based systems engineering (MBSE)

Literature study on the potential of Artificial Intelligence in Scenario-Technique - Gräßler, Iris; Tusek, Alena Marie; Thiele, Henrik; Preuß, Daniel; Grewe, Benedikt; Hieb, Michael (XXXIII ISPIM Innovation Conference Proceedings)

Fortschrittskontrolle der Modellierung mechatronischer Produkte - Gräßler, Iris; Wiechel, Dominik; Thiele, Henrik (Tagungsband der Fachtagung VDI-Mechatronik)
Die Anforderungen an die Entwicklung mechatronischer Systeme sind seit der Erstfassung der VDI Richtlinie 2206 im Jahr 2004 stetig gestiegen. Nach einer umfassenden Überarbeitung ist 2021 die Richtline im Weißdruck neu veröffentlicht worden. Neben dem Systemdenken als gestärktes Kernelement des V-Modells und sechs Kontrollpunkten nur Gliederung der sachlogischen Aufgaben ist die durchgängig explizite „Modellierung und Analyse“ eine wesentliche Neuerung der Richtlinie. Da sich die Kontrollfragen nur auf den Entwicklungsprozess im Ganzen beziehen, wird durch die Betrachtung der Modellierung eines Batteriesystems aus einem Entwicklungsprojekt eines deutschen Automobilherstellers die folgende Forschungsfrage betrachtet: Welche spezifischen Kontrollfragen zu Fortschritt und Reifegrad der Modellierung eines Batteriesystems können aus den Kontrollpunkten des V-Modells (VDI 2206:2020) gefolgert werden? Als Ergebnis der Forschung liegen hinsichtlich der Modellierung eines spezifischen Systems detaillierte Kontrollfragen vor, die eine methodische Unterstützung für die modellbasierte Systementwicklung komplexer mechatronischer Systeme bieten. Zusätzlich ermöglichen sie der Projektleitung die Überprüfung des aktuellen Status der Entwicklung und sichern die Vollständigkeit des Systemmodells ab.

Supporting Innovation Management for SMEs: A Tool for Idea Selection - Gräßler, Iris; Koch, Anna-Sophie; Thiele, Henrik; Dattner, Michael (Proceedings of the ISPIM Innovation Conference)
In innovation management, usually there is a large number of product ideas, not all of which meet the requirements of a company and make sense to pursue further. For selecting the most promising ideas, several methods exist which each focus on a certain aspect. Due to the characteristics of Small and Medium Enterprises (SMEs) such as limited resources, these enterprises have special requirements on methods for selecting ideas. In this study, criteria of SMEs for idea selection are deducted from SME-characteristics. Methods for idea selection are tested for fulfillment of these criteria and the results are combined in a matrix. Together with a guideline, a tool for idea selection in innovation management of SMEs is developed. The results are validated in the context of innovation management in SMEs. By selecting a method, a SME is enabled to make economically viable decisions for their product portfolio, thus ensuring sustainable economic success.
Keywords: innovation management; SME; evaluation method; idea selection; meta-study; idea evaluation

Produktspezifische Optimierung der Nachhaltigkeit im Ersatzteilmanagement. Ganzheitliche Vorgehensweise zur Bewertung der Nachhaltigkeit additiv gefertigter Komponenten für den Aftermarket - Gräßler, Iris; Hillebrand, Stefan; Thiele, Henrik (Digitalisierung im Kontext von Nachhaltigkeit und Klimawandel)

V-model based development of cyber-physical systems and cyber-physical production systems - Gräßler, Iris; Wiechel, Dominik; Roesmann, Daniel; Thiele, Henrik (Procedia CIRP)
Challenges of the development of mechatronic systems and corresponding production systems have increased steadily. Changes are primarily due to increased product complexity and the connection to the internet of things and services, enabling Cyber-Physical Systems (CPS) and Cyber-Physical Production Systems (CPPS). Major innovations of the revised VDI guideline 2206 for developing mechatronic systems are systems thinking as a core element and six checkpoints for structuring deliverables along the V-Model. These checkpoints serve for orientation in result progress and thus enable a structured and complete development process. However, tasks and checkpoints of the new guideline focus on the product development itself without integrating the development of related CPPS, enabling optimization simultaneously to system development. Implications are derived by a three-step analysis. The paper at hand contributes fundamental extensions of the checkpoint questions regarding integrated CPPS development. These questions provide methodical support for system developers of CPPS for CPS by enabling the project manager to check the status, schedule further development steps and evaluate the maturity of the whole, integrated development.
Keywords: Cyber-Physical Production System (CPPS); V-Model; Product System Development; Integrated Development; VDI 2206

VDI/VDE 2206 - Entwicklung mechatronischer und cyber-physischer Systeme - Gräßler, Iris; Hentze, Julian; Hesse, Philipp; Preuß, Daniel; Thiele, Henrik; Wiechel, Dominik; Bothen, Martin; Bruckmann, Tobias; Dattner, Michael; Ehl, Thomas; Hawlas, Martin; Krimpmann, Christoph; et al.

Semi-automatized consistency assessment in Scenario-Technique: Generic consistency patterns and user types - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (ISPIM Conference Proceedings)

Scenario Technique - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (Integrated Design Engineering. Interdisciplinary and Holistic Product Development)

Automation 2030. Zukunft gestalten - Szenarien und Empfehlungen - Gräßler, Iris; Thiele, Henrik; al., et.

Innovation management and strategic planning of innovative self-preparednes and self-Protection services - Gräßler, Iris; Pottebaum, Jens; Scholle, Philipp; Thiele, Henrik (ISPIM Conference Proceedings; 7. - 10. Jun. 2020)

ASSESSING THE FUTURE: METHODS AND CRITERIA - Gräßler, Iris; Thiele, Henrik; Scholle, P. (Proceedings of the DESIGN 2020 16th International Design Conference)
Abstract As time-to-market is getting shorter, customer needs have to be identified as early as possible in product development. Correctly applied, corporate foresight can give a glimpse into the future to anticipate such needs and thus gain a competitive advantage. A support tool to choose the appropriate method of foresight is not available yet. Thus, a literature study on foresight methods in industry is performed and a novel decision support tool is proposed which avoids high entrepreneurial risks. Based on the findings, potentials for future work are identified for different types of methods.

A Scrum Agile Integrated Development Framework - Thiele, Henrik; Weber, Sebastian; Reichwein, Jannik; Bartolo, Joseph A.; Tchana, Yvan; Jimenez, Lucas; Borg, Jonathan C. (Proceedings of the DESIGN 2020 16th International Design Conference, 26. - 29. Okt. 2020)

Improving scenario-technique by a semi-automatized consistency assessment based on pattern recognition by artificial neural networks - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (Proceedings of the DESIGN 2020 16th International Design Conference; 26. - 29. Okt. 2020)

Methode zur Einflussanalyse in der Szenario-Technik auf Basis gerichteter Graphen - Gräßler, Iris; Thiele, Henrik; Scholle, Philipp (Design fox X - Beiträge zum 30. DfX-Symposium September 2019, Band 30)

Strategische Planung in Plattformen und Eco-Systemen mittels Szenario-Technik - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (Fachtagung Mechatronik 2019 Paderborn)
Die Digitalisierung mechatronischer Produkte und der Trend zu Plattformen und Eco-Systemen stellt die Anbieter der Produkte vor die Herausforderung, neue digitale Geschäftsmodelle zu planen und neue Produkte erfolgreich am Markt zu platzieren. In diesem Beitrag wird ein Werkezug zur strategischen Planung mittels Szenario-Technik vorgestellt, welches direkt mit einer Datenplattform verknüpft ist. Den Anbietern von mechatronischen Systemen, welche die Dienste der Plattform nutzen wollen, um einen „Mehrwert“ für ihre Produkte zu erzeugen, wird so ein Werkzeug zur effizienten strategischen Planung zur Verfügung gestellt. Durch die Anbindung an die Plattform werden generische Einflussfaktoren und Selektionsregeln für die Anwender bereitgestellt, um aufwandsminimal selbstständig Zukunftsszenarien zu antizipieren und Geschäftschancen zu erkennen. Das integrierte Werkzeug zur strategischen Planung wird auf Basis der Fallstudie für das mechatronische Produkt eines low-cost Hochwasserschutzsystems, welches auf eine paneuropäische Datenplattform zugreift, validiert.

Method for Analysing Requirement Change Propagation based on a Modified Pagerank Algorithm - Gräßler, Iris; Thiele, Henrik; Oleff, Christian; Scholle, Philipp; Schulze, Veronika (Proceedings of the Design Society: International Conference on Engineering Design)
Complexity of products and systems is increasing through digitalization, interdisciplinarity as well as high technology maturity and new business models. In consequence, new product development (NPD) projects need to manage and satisfy a large number of requirements from a broad range of stakeholders. Yet, NPD projects are often delayed due to requirement changes. In this paper, a new method for analyzing requirement change propagation is presented. The method is based on the assessment of requirement interrelations structured in a requirements structure matrix by a modified page-rank algorithm. By the method, a high number of strongly interrelated requirements can be analyzed in an efficient manner. Additionally, higher-level interrelations as well as the relative weights of requirements are also incorporated in the analysis. Hereby, an efficient holistic approach towards the analysis of requirement change propagation is proposed.